Upaya meningkatkan hasil belajat matematika melalui model project based learning (PjBL) pada siswa kelas 5 SD Negeri 1 Towangsan - Nabilah Putri Febriyani (Universitas Sebelas Maret, 2024)
The goal of this study is to enhance the mathematics academic performance of fifth-grade students at SD Negeri 1 Towangsan through the implementation of a project-based learning approach. The research methodology employed is classroom action research conducted over 2 cycles. Each cycle includes four stages: planning, taking action, evaluating, and reflecting. This study involved 18 students in fifth grade at an elementary school. The methods of collecting data include observing students and teachers, administering tests to assess student progress, and keeping records. The information collected was subsequently examined using descriptive statistical analysis methodsAccording to the findings from the research, there has been a 16.66% improvement in learning outcomes. In the first cycle, 66.67% of the learning outcomes were achieved, while in the second cycle, the achievement rate increased to 83.33%. Therefore, it can be inferred that utilizing the project based learning (PjBL) approach can enhance students' academic performance.